Parent Artery Curvature Influences Inflow Zone Location of Unruptured Sidewall Internal Carotid Artery Aneurysms - Futami, K. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Future aneurysmal behaviors or treatment outcomes of cerebral aneurysms may be related to the hemodynamics around the inflow zone. Here we investigated the influence of parent artery curvature on the inflow zone location of unruptured sidewall internal carotid artery aneurysms. MATERIALS AND METHODS: In 32 aneurysms, the inflow zone location was decided by 4D flow MR imaging, and the radius of the parent artery curvature was measured in 2D on an en face image of the section plane corresponding to the aneurysm orifice. RESULTS: The inflow zone was on the distal neck in 10 (group 1, 31.3%), on the lateral side in 19 (group 2, 59.4%), and on the proximal neck in 3 (group 3, 9.4%) aneurysms. The radius in group 1 was significantly larger than that in group 2 (8.3 mm [4.5 mm] versus 4.5 mm [1.9 mm]; median [interquartile range]; P < .0001). All 7 aneurysms with a radius of >8.0 mm were in group 1. All 18 aneurysms with a radius of <6.0 mm were in group 2 or 3. In two group 3 aneurysms, the inflow zone was located in a part of the neck extending beyond the central axis of the parent artery. CONCLUSIONS: The inflow zone locations of sidewall aneurysms can be influenced by the parent artery curvature evaluated in 2D on an en face image of the section plane corresponding to the aneurysm orifice.